Leydig cell ovarian tumor – clinical case description and literature review - Klimek, Mateusz; Radosz, Patrycja; Lemm, Magdalena; Szanecki, Wojciech; Dudek, Aleksandra; Pokładek, Sandra; Piwowarczyk, Maria; Poński, Michał; Cichoń, Bartosz; Kajor, Maciej; Witek, Andrzej (Menopause Review/Przegląd Menopauzalny, 2020)
Leydig cell ovarian tumors constitute not only a medical problem for clinicians but also a social problem – which is why women with symptoms of hirsutism relatively quickly contact physicians for medical consultation. Leydig cell ovarian tumor is a rare sex cord-gonadal stromal tumor which constitutes less than 0.5% of ovarian tumors. These cancers appear at all ages but the majority of the cases concern women in the perimenopause. In the majority of cases (70-85%), the growth is accompanied by androgen secretion, together with virilization and hirsutism. The presence of hormonally active ovarian cancers should be suspected in cases of rapidly growing symptoms of masculinization, especially when the level of free testosterone in the blood exceeds the upper limit for the given age more than three times. In diagnosing postmenopausal hyperandrogenism, it is necessary to take into account hormonally active ovarian tumors, as well as adrenal cancers. It is important to exclude other causes of hyperandrogenism, e.g. endocrinopathies (acromegaly or hypothyroidism), or iatrogenic and idiopathic factors. In order to make the diagnosis and implement the proper treatment method faster, an interdisciplinary team of physicians specializing in endocrinology, gynecology and oncology is crucial. This paper contains a study of two cases concerning Leydig cell ovarian tumors in women of postmenopausal age with symptoms of masculinization and hirsutism.